Host response to influenza infections in human blood: association of influenza severity with host genetics and transcriptomic response - Schughart, Klaus; Smith, Amber M.; Tsalik, Ephraim L.; Threlkeld, Stephen C.; Sellers, Subhashini; Fischer, William A.; Schreiber, Jens; Lücke, Eva; Cornberg, Markus; Debarry, Jennifer; Woods, Christopher W.; McClain, Micah T.; et al. (Frontiers in Immunology, 2024)
Influenza virus infections are a major global health problem. Influenza can result in mild/moderate disease or progress to more severe disease, leading to high morbidity and mortality. Severity is thought to be primarily driven by immunopathology, but predicting which individuals are at a higher risk of being hospitalized warrants investigation into host genetics and the molecular signatures of the host response during influenza infections. Here, we performed transcriptome and genotype analysis in healthy controls and patients exhibiting mild/moderate or severe influenza (ICU patients). We identified 169 differentially expressed genes and related molecular pathways between patients in the ICU and those who were not in the ICU. A unique aspect of our study was the genotyping of all participants, which allowed us to assign ethnicities based on genetic variation and assess whether the variation was correlated with expression levels. The analysis identified 871 genes associated to a genetic variant and 39 genes distinct between African-Americans and Caucasians. We also investigated the effects of age and sex and found only a few discernible gene effects in our cohort. Together, our results highlight select risk factors that may contribute to an increased risk of ICU admission for influenzainfected patients. This should help to develop better diagnostic tools based on molecular signatures, in addition to a better understanding of the biological processes in the host response to influenza. Introduction Influenza virus infections represent a major global health problem. High morbidity and mortality are observed, with up to 500,000 deaths each year worldwide (Iuliano et al., 2018) and millions during past pandemics (Taubenberger and Morens, 2008;Jackson et al., 2021). Influenza infections cause a range of disease phenotypes that range from asymptomatic to severe. Severity is influenced by a variety of viral and host factors, including influenza strain, age, sex, host genetics, and immune status (e.g. (Srivastava et al., 2009;Fukuyama and Kawaoka, 2011;Kuiken et al., 2012;Betakova et al., 2017;Park and Ryu, 2018). Mortality in severe cases is primarily driven by a pathological immune response characterized by high levels of neutrophils, macrophages, and inflammatory cytokines (de